The utilization of social media in improving adolescent social interaction with parents - Deni Suryanto; Ahmad Rozai’e Akbar; Dawami; Izzah Nur Aida Zur Raffar; Salasiah Hanin Hamjah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social media is prevalent in the Industrial Revolution 4.0 era as a confluence of communication and technological currents. On the one hand, the fast advancement of technology has a beneficial influence and impact on the development of adolescent social contacts with both parents, such as communication ethics, how to behave and engage. Neglecting to guidance and supervision for adolescent in their use of social media would result in each youngster being undirected and prone to selfishness, apathy, racism, intolerance, sexual and criminal aberrations. This study intends to investigate how the mean of social media in adolescence improves the social interaction of parenthood using descriptive methods. Based on the findings of researchers and expert opinions, it is proposed that one form of social media use in adolescents is improving social interactions towards fatherhood that must be possessed is the ability to use social media as a stimulation tool in increasing intellectual, emotional, and spiritual intelligence in adolescent identity. This study's consequences can undoubtedly give a foundation of information for educational institutions and families in fostering positive social relationships between teenagers and both parents. This research, which may be shared and practiced, is also expected to make a significant contribution to the parties concerned in enhancing the social relationships of adolescent children.